Impact of Annealing Temperature on the Morphological, Optical and Photoelectrochemical Properties of Cauliflower-like CdSe0.6Te0.4 Photoelectrodes; Enhanced Solar Cell Performance - Gajanan S. Ghodake (MDPI AG, 2021)
We are reporting on the impact of air annealing temperatures on the physicochemical properties of electrochemically synthesized cadmium selenium telluride (CdSe0.6Te0.4) samples for their application in a photoelectrochemical (PEC) solar cell. The CdSe0.6Te0.4 samples were characterized with several sophisticated techniques to understand their characteristic properties. The XRD results presented the pure phase formation of the ternary CdSe0.6Te0.4 nanocompound with a hexagonal crystal structure, indicating that the annealing temperature influences the XRD peak intensity. The XPS study confirmed the existence of Cd, Se, and Te elements, indicating the formation of ternary CdSe0.6Te0.4 compounds. The FE-SEM results showed that the morphological engineering of the CdSe0.6Te0.4 samples can be achieved simply by changing the annealing temperatures from 300 to 400 °C with intervals of 50 °C. The efficiencies (ƞ) of the CdSe0.6Te0.4 photoelectrodes were found to be 2.0% for the non-annealed and 3.1, 3.6, and 2.5% for the annealed at 300, 350, and 400 °C, respectively. Most interestingly, the PEC cell analysis indicated that the annealing temperatures played an important role in boosting the performance of the photoelectrochemical properties of the solar cells.